Poly(3-hexylthiophene) (P3HT): fruit fly or outlier in organic solar cell research?. Issue 23 (17th November 2016) - Kleinschmidt, Andrew T.; Root, Samuel E.; Lipomi, Darren J.
Abstract : Regioregular poly(3-hexylthiophene) (P3HT) is used as a model polymer for research in organic solar cells. Abstract : Regioregular poly(3-hexylthiophene) (P3HT) is used as a model polymer for research in organic solar cells. It is popular despite its dissimilarity in many respects to the high-performing class of polymers based on the donor–acceptor (DA) motif. For example, P3HT has a low glass-transition temperature, is highly crystalline for a semiconducting polymer, is made by a living polymerization, and contains no fused rings along the conjugated backbone; these characteristics stand in contrast to most DA polymers. These differences in structure and morphology suggest that many of the results obtained for P3HT are not directly transferable to the design and processing of new materials. This highlight proposes that focusing on a few examples of conjugated polymers based in part on the way these materials assemble in the solid state would enable greater transferability of the results from one study to another. That is, the field would benefit from having more than one "fruit fly."